War generation of personnel working in the all Russian FMD research institute, FGBI «Federal centre for animal health» (devoted to 70th Anniversary of the Great Patriotic War) - A. M. Rakhmanov; B. A. Glushko (Ветеринария сегодня)
The article presents information about the personnel of the FMD Research Institute and FGBI «ARRIAH» - veterans of the Great Patriotic War, home-front workers and children born during the war.